Hysteria and identity formation in selected novels by Fay Weldon and Nawal El Saadawi - Abdullah, Omar Mohammed (2016)
Hysteria is a quite common phenomenon that prevailed in the twentieth century literature, as such, for its importance, it needs to be highlighted. This thesis focuses on the female authored texts that knit hysteria in the very fabric of their material.I argue that patriarchy, subjugation, sexual violation and the resulting psychologica disturbance, gnaw females‘ subjectivity and help in enacting hysteria intentionally or otherwise. Fay Weldon and Nawal El Saadawi are postmodern feminist contemporary writers, focusing on the problems and maladies of women.In Weldon‘s Praxis and The Life and Loves of a She- Devil, and El Saadawi's Woman at Point Zero and God Dies by the Nile, hysteria surfaces on female characters‘ bodies revealing the shortcomings and problems they suffer from. In this study, hysteric subjects tear the norms imposed by individuals or the society and transform from silent subjects into revolutionary individuals. Because their bodies are invaded and haunted, female characters cannot speak and even if they can, they will not be heard. Consequently, they develop a hysteric body language and reflect what their tongues could not communicate. Using Freud‘s and Irigaray‘s concepts of hysteria alongside with Kristeva‘s concept of Abjection, I will investigate what drives women to be hysterics. Is it a consequence of sexual fantasies and a result of an earlier trauma as Freud theorized? Or is it a protest that comes out of repression and silencing practiced by the society as Irigaray puts it? What role does Abjection play in initiating or healing hysteria and absolving the subject? How can hysteria be inferred through Freudian and Irigarian ideas in certain texts? Investigating hysteria according to these readings has shown the reasons that fall behind the infliction of hysteria and simultaneously revealed, through abjection, how new identities are restructured. The hysterics rebelled against degradation, suppression and exploitation using the body as the only medium of expression and managed to restructure and actualize themselves by employing abjection. Hence, this expressive subversion becomes women's strategy to reclaim power.